A graphene-based thermal conductive film and preparation method thereof
By partially reducing graphene oxide and adding modified materials, the graphene thermal conductivity film was prepared by thermal spraying, and through foaming and reduction treatment, the problem of poor thermal conductivity and mechanical properties in the prior art was solved, achieving high Graphene thermal conductivity and excellent mechanical properties.
Patent Information
- Application Number
- CN202311043323.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-08-18
AI Technical Summary
In the existing preparation methods for graphene thermal conductivity films, additives cause thermal conductivity to decrease, making it difficult to prepare high-thickness films, and defects are prone to occur during the transfer process and poor mechanical properties.
By partially reducing the graphene oxide, modified carbon fiber, nanocellulose and silver nitrate were added, graphene oxide composite film was prepared by thermal spraying, and foaming and potassium iodide reduction treatment, and finally hydrogen replacement treatment was used to improve heat conductivity rate and mechanical properties.
It achieves high thermal conductivity and excellent mechanical properties, solves the problem that additives affect thermal conductivity, is suitable for large-area film preparation, and improves the stability and transfer performance of the film.
Smart Images

Figure BDA0004401553290000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene materials, and in particular to a graphene-based thermal conductive film and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, electronic devices are gradually developing towards miniaturization, component integration, lightness, and high performance. However, electronic devices will generate a lot of heat during operation. If the heat cannot be effectively discharged in time, it will not only affect its stability, but also greatly shorten its service life. In other words, the performance and reliability of electronic products are increasingly subject to thermal conductivity issues. Therefore, heat dissipation materials must be used to improve heat transfer efficiency, eliminate hot spot accumulation, quickly dissipate heat, reduce device temperature, and enable long-term and efficient operation.
[0003] Currently, the most widely used and mature thermal conductive material is graphite thermal conductive film. This product is a sheet material with extremely high thermal conductivity made by repeatedly heat-treating a polymer film of carbon material under special sintering conditions. It has the characteristics of thin thickness, high thermal conductivity efficiency and light weight.
[0004] Graphene is a carbon atom in the form of sp 2 The hybrid orbitals form a single-layer planar film arranged in a hexagonal honeycomb lattice, a two-dimensional material with a thickness of only one carbon atom. Graphene is currently the thinnest but hardest nanomaterial in the world, with excellent physical and chemical properties. At the same time, graphene materials have high strength and good flexibility. The prepared graphene film has the characteristics of high strength and flexibility, high temperature resistance, small expansion coefficient, good thermal and electrical conductivity, and stable chemical properties. In this context, graphene thermal conductive film quickly replaced traditional thermal conductive materials. Graphene thermal conductive film has high thermal conductivity in the horizontal direction of electronic products, and its thermal conductivity in the vertical direction is higher than that of traditional thermal conductive materials.
[0005] At present, the preparation methods of graphite thermal conductive films mainly include coating method, filtration method and CVD method. The coating method includes pulling, spin coating, scraper and other methods. The difficulty lies in how to configure a stable and non-agglomerated graphene slurry, which requires the addition of thickeners, surfactants, adhesives and other additives to the slurry, but these additives will prevent graphene or graphene oxide from being well connected together; and due to the steric hindrance of the additives, the graphene layers cannot be overlapped in an orderly manner parallel to the substrate, which will greatly reduce the thermal conductivity of the heat dissipation film; in addition, the spin coating method is not suitable for the preparation of large-area films, and the filtration method is time-consuming and difficult to control the film thickness. The cost of preparing thermal conductive films by CVD is relatively high. Generally, graphene is grown on a substrate in one or more layers using the CVD method. It is difficult to form a very thick graphene layer, which is generally several hundred nanometers thick. Therefore, it is not suitable for preparing heat dissipation films, but is mainly used for conductive films. At the same time, the preparation of thermal conductive films by CVD also faces the problem of transfer before use. It must be transferred from the metal substrate to the required substrate before the processing device can be used, and the transfer will bring more defects to the thermal conductive film.
[0006] Patent CN104085143B discloses a method for preparing a graphene composite thermal conductive film, which includes pre-oxidizing flake graphite or graphite powder, further oxidizing the pre-oxidized graphite using the Hummers method, and preparing an aqueous solution of graphene oxide. The aqueous solution of graphene oxide is then sprayed on a substrate using a thermal spraying method to deposit a graphene oxide film, which is then reduced and coated. However, there are still many pores remaining in the preparation process of this patent, which affects the thermal conductivity. The mechanical properties of the thermal conductive film are also poor and it is very easy to be damaged. Summary of the invention
[0007] The purpose of the present invention is to provide a graphene-based thermally conductive film and a preparation method thereof, which has high thermal conductivity and excellent mechanical properties.
[0008] To achieve the above object, the present invention is implemented by the following scheme:
[0009] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0010] (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution;
[0011] (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, and then adding the modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution;
[0012] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0013] (4) The graphene oxide composite film is then subjected to a foaming treatment, and then reduced using a potassium iodide solution. Finally, the composite film is sandwiched between two graphite sheets and transferred as a whole to a sealed container. The composite film is replaced using hydrogen to obtain the graphene-based thermal conductive film.
[0014] Preferably, in parts by weight, the specific method of step (1) is as follows: first, 1 part of graphene oxide, 0.8-1 part of magnesium powder, 0.8-1 part of diethylenetriamine, 0.05-0.08 part of N,N-diisopropylethylamine, and 0.08-0.1 part of 3-5% palladium carbon catalyst are added to 100 parts of deionized water, stirred at 50-60° C. for 50-70 minutes, allowed to stand, filtered, washed, 100 parts of deionized water are added, and ultrasonic vibration is applied evenly to obtain the graphene oxide aqueous solution.
[0015] More preferably, the process conditions for standing still are: standing still at 0-4°C for 30-40 minutes; and the process conditions for ultrasonic oscillation are: ultrasonic oscillation at 300-500W for 15-20 minutes.
[0016] Preferably, in step (2), the preparation method of the modified carbon fiber is as follows, in parts by weight: first, 1 part of ethylene glycol monoethyl ether and 1 to 2 parts of ethyl acetate are stirred and mixed, then 0.02 to 0.04 parts of carbon fiber are added, heated and refluxed for 3 to 5 hours, centrifuged, washed, and dried to obtain the modified carbon fiber.
[0017] Preferably, in step (2), the carbon content of the carbon fibers is greater than 95%, and the average length is 4 to 8 mm; the diameter of the nano carbon fibers is 5 to 8 nm, and the length is 1 to 2 μm.
[0018] Preferably, in step (2), the mass ratio of modified carbon fiber, nanocellulose, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.1-0.2: 0.05-0.08: 0.03-0.05: 0.06-0.09:100.
[0019] Preferably, in step (2), the process conditions of ultrasonic oscillation are: 300-500W ultrasonic oscillation for 20-30 minutes.
[0020] Preferably, in step (3), the specific process conditions of thermal spraying are: the spraying height is 45 to 55 cm from the substrate, and the temperature is 130 to 140°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the airflow size of the entire air path, and the air pressure is 0.6 to 0.8 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.3 to 0.5 MPa.
[0021] Preferably, in step (3), the flexible substrate is polyethylene terephthalate or polybutylene terephthalate.
[0022] Preferably, in step (4), the process conditions for the foaming treatment are: foaming at 200-250° C. for 80-100 minutes.
[0023] Preferably, in step (4), the specific method of reduction is as follows, in parts by weight: placing 1 part of the foamed graphene oxide composite film flat in 5 to 8 parts of a 5 to 8% potassium iodide solution, and oscillating ultrasonically at 60 to 70° C. and 200 to 300 W for 30 to 40 minutes.
[0024] Preferably, in step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container is 15-20 MPa, maintain the pressure for 5-8 minutes, evacuate again, introduce hydrogen and maintain the pressure, and repeat this 3-5 times.
[0025] A graphene-based thermally conductive film is obtained using the above preparation method.
[0026] The beneficial effects of the present invention are:
[0027] The present invention first partially reduces graphene oxide to prepare a graphene oxide aqueous solution; then, carbon fiber is modified by ethylene glycol monoethyl ether to obtain modified carbon fiber; then, modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide are added to the graphene oxide aqueous solution, ultrasonically oscillated evenly, and a premixed liquid is obtained; then, the premixed liquid is sprayed on a flexible substrate by a thermal spraying method to obtain a graphene oxide composite film; then, the graphene oxide composite film is foamed, and then reduced by potassium iodide solution, and finally sandwiched between two graphite sheets, and the whole is transferred to a closed container, and hydrogen is used for replacement treatment to obtain a graphene-based thermal conductive film. The thermal conductive film has a high thermal conductivity and good mechanical properties.
[0028] Because graphene has poor dispersibility in water, the present invention uses graphene oxide as the starting material, and the double bond benzene at the edge carbon atoms and the middle active carbon atoms of graphene oxide is oxidized to epoxy groups, and the edge carbon atoms such as hydroxyl groups are oxidized to carboxyl groups. Due to the presence of these groups, its water solubility is improved, but it is also not conducive to the dispersion of graphene oxides and affects film formation. Therefore, the present invention first performs a partial reduction treatment on graphene oxide, which is conducive to film formation and ensures the thermal conductivity of the product.
[0029] Graphene oxide itself contains lattice defects, which directly affect heat conduction and reduce thermal conductivity. The present invention introduces modified carbon fiber, nanocellulose and silver nitrate, wherein silver doping can connect the broken thermal conduction path, improve thermal conductivity, and improve mechanical properties at the same time. Modified carbon fiber and nanocellulose have good hydrophilicity, which can reduce graphene agglomeration on the one hand, and improve orientation on the other hand, promote oriented film formation, and further improve thermal conductivity and mechanical properties.
[0030] Under the foaming effect of azodicarbonamide, the distance between graphene oxide is further increased. Combined with subsequent reduction and hydrogen replacement treatment, the air remaining in the pores is fully removed, further improving the thermal conductivity of the product. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0034] (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution;
[0035] (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, and then adding the modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution;
[0036] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0037] (4) The graphene oxide composite film is then subjected to a foaming treatment, and then reduced using a potassium iodide solution. Finally, the composite film is sandwiched between two graphite sheets and transferred as a whole to a sealed container. The composite film is replaced using hydrogen to obtain the graphene-based thermal conductive film.
[0038] The specific method of step (1) is as follows: first, 1 g of graphene oxide, 0.8 g of magnesium powder, 1 g of diethylenetriamine, 0.05 g of N,N-diisopropylethylamine, and 0.1 g of 3% palladium carbon catalyst are added to 100 g of deionized water, stirred at 60° C. for reaction for 50 minutes, allowed to stand, filtered, washed, 100 g of deionized water is added, and ultrasonic vibration is performed evenly to obtain the graphene oxide aqueous solution.
[0039] The process conditions for standing still are: standing still at 4° C. for 30 minutes; the process conditions for ultrasonic oscillation are: ultrasonic oscillation at 500 W for 15 minutes.
[0040] In step (2), the preparation method of the modified carbon fiber is as follows: first, 1 g of ethylene glycol monoethyl ether and 2 g of ethyl acetate are stirred and mixed, then 0.02 g of carbon fiber is added, heated and refluxed for 5 hours, centrifuged, washed, and dried to obtain the modified carbon fiber.
[0041] In step (2), the carbon content of the carbon fiber is greater than 95%, and the average length is 4 mm; the diameter of the nano carbon fiber is 8 nm, and the length is 1 μm.
[0042] In step (2), the mass ratio of modified carbon fiber, nanocellulose, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.2:0.05:0.05:0.06:100.
[0043] In step (2), the process conditions of ultrasonic oscillation are: 500W ultrasonic oscillation for 20 minutes.
[0044] In step (3), the specific process conditions of thermal spraying are: the spraying height is 55 cm from the substrate and the temperature is 130°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire gas path, the air pressure is 0.8 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.3 MPa.
[0045] In step (3), the flexible substrate is polyethylene terephthalate.
[0046] In step (4), the process conditions for the foaming treatment are: foaming at 250° C. for 80 minutes.
[0047] In step (4), the specific method of reduction is: placing 1 g of the foamed graphene oxide composite film flat in 8 g of a 5% potassium iodide solution, and oscillating ultrasonically at 70° C. and 200 W for 30 minutes.
[0048] In step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container reaches 20 MPa, maintain the pressure for 5 minutes, evacuate the container again, introduce hydrogen and maintain the pressure, and repeat this process 5 times.
[0049] Example 2
[0050] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0051] (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution;
[0052] (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, and then adding the modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution;
[0053] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0054] (4) The graphene oxide composite film is then subjected to a foaming treatment, and then reduced using a potassium iodide solution. Finally, the composite film is sandwiched between two graphite sheets and transferred as a whole to a sealed container. The composite film is replaced using hydrogen to obtain the graphene-based thermal conductive film.
[0055] The specific method of step (1) is as follows: first, 1 g of graphene oxide, 1 g of magnesium powder, 0.8 g of diethylenetriamine, 0.08 g of N,N-diisopropylethylamine, and 0.08 g of 5% palladium carbon catalyst are added to 100 g of deionized water, stirred at 50° C. for 70 minutes, allowed to stand, filtered, washed, 100 g of deionized water is added, and ultrasonic vibration is applied evenly to obtain the graphene oxide aqueous solution.
[0056] The process conditions for standing still are: standing still at 0°C for 40 minutes; the process conditions for ultrasonic oscillation are: ultrasonic oscillation at 300W for 20 minutes.
[0057] In step (2), the preparation method of the modified carbon fiber is as follows: first, 1 g of ethylene glycol monoethyl ether and 1 g of ethyl acetate are stirred and mixed, then 0.04 g of carbon fiber is added, heated and refluxed for 3 hours, centrifuged, washed, and dried to obtain the modified carbon fiber.
[0058] In step (2), the carbon content of the carbon fibers is greater than 95% and the average length is 8 mm; the diameter of the nano carbon fibers is 5 nm and the length is 2 μm.
[0059] In step (2), the mass ratio of modified carbon fiber, nanocellulose, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.1:0.08:0.03:0.09:100.
[0060] In step (2), the process conditions of ultrasonic oscillation are: 300W ultrasonic oscillation for 30 minutes.
[0061] In step (3), the specific process conditions of thermal spraying are: the spraying height is 45 cm from the substrate and the temperature is 140°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire air path, the air pressure is 0.6 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.5 MPa.
[0062] In step (3), the flexible substrate is polybutylene terephthalate.
[0063] In step (4), the process conditions of the foaming treatment are: foaming at 200° C. for 100 minutes.
[0064] In step (4), the specific method of reduction is: placing 1 g of the foamed graphene oxide composite film flat in 5 g of 8% potassium iodide solution, and oscillating ultrasonically at 60° C. and 300 W for 40 minutes.
[0065] In step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container reaches 15 MPa, maintain the pressure for 8 minutes, evacuate again, introduce hydrogen and maintain the pressure, and repeat this 3 times.
[0066] Example 3
[0067] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0068] (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution;
[0069] (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, and then adding the modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution;
[0070] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0071] (4) The graphene oxide composite film is then subjected to a foaming treatment, and then reduced using a potassium iodide solution. Finally, the composite film is sandwiched between two graphite sheets and transferred as a whole to a sealed container. The composite film is replaced using hydrogen to obtain the graphene-based thermal conductive film.
[0072] The specific method of step (1) is as follows: first, 1 g of graphene oxide, 0.9 g of magnesium powder, 0.9 g of diethylenetriamine, 0.06 g of N,N-diisopropylethylamine, and 0.09 g of 4% palladium carbon catalyst are added to 100 g of deionized water, stirred at 55° C. for 60 minutes, allowed to stand, filtered, washed, 100 g of deionized water is added, and ultrasonic vibration is applied evenly to obtain the graphene oxide aqueous solution.
[0073] The process conditions for standing still are: standing still at 2° C. for 35 minutes; the process conditions for ultrasonic oscillation are: ultrasonic oscillation at 400 W for 18 minutes.
[0074] In step (2), the preparation method of the modified carbon fiber is as follows: first, 1 g of ethylene glycol monoethyl ether and 1.5 g of ethyl acetate are stirred and mixed, then 0.03 g of carbon fiber is added, heated and refluxed for 4 hours, centrifuged, washed, and dried to obtain the modified carbon fiber.
[0075] In step (2), the carbon content of the carbon fibers is greater than 95% and the average length is 6 mm; the diameter of the nano carbon fibers is 7 nm and the length is 1.5 μm.
[0076] In step (2), the mass ratio of modified carbon fiber, nanocellulose, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.15:0.07:0.04:0.08:100.
[0077] In step (2), the process conditions of ultrasonic oscillation are: 400W ultrasonic oscillation for 25 minutes.
[0078] In step (3), the specific process conditions of thermal spraying are: the spraying height is 50 cm from the substrate and the temperature is 135°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire gas path, the air pressure is 0.7 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.4 MPa.
[0079] In step (3), the flexible substrate is polyethylene terephthalate.
[0080] In step (4), the process conditions for the foaming treatment are: foaming at 220° C. for 90 minutes.
[0081] In step (4), the specific method of reduction is: placing 1 g of the foamed graphene oxide composite film flat in 7 g of a 6% potassium iodide solution, and oscillating ultrasonically at 65° C. and 200 W for 35 minutes.
[0082] In step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container reaches 18 MPa, maintain the pressure for 6 minutes, evacuate again, introduce hydrogen and maintain the pressure, and repeat this 4 times.
[0083] Comparative Example 1
[0084] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0085] (1) first preparing graphene oxide into a graphene oxide aqueous solution;
[0086] (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, and then adding the modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution;
[0087] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0088] (4) The graphene oxide composite film is then subjected to a foaming treatment, and then reduced using a potassium iodide solution. Finally, the composite film is sandwiched between two graphite sheets and transferred as a whole to a sealed container. The composite film is replaced using hydrogen to obtain the graphene-based thermal conductive film.
[0089] The specific method of step (1) is as follows: first, 1 g of graphene oxide is added into 100 g of deionized water, and ultrasonic vibration is applied uniformly to obtain the graphene oxide aqueous solution.
[0090] The process conditions of ultrasonic oscillation are: 500W ultrasonic oscillation for 15 minutes.
[0091] In step (2), the preparation method of the modified carbon fiber is as follows: first, 1 g of ethylene glycol monoethyl ether and 2 g of ethyl acetate are stirred and mixed, then 0.02 g of carbon fiber is added, heated and refluxed for 5 hours, centrifuged, washed, and dried to obtain the modified carbon fiber.
[0092] In step (2), the carbon content of the carbon fiber is greater than 95%, and the average length is 4 mm; the diameter of the nano carbon fiber is 8 nm, and the length is 1 μm.
[0093] In step (2), the mass ratio of modified carbon fiber, nanocellulose, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.2:0.05:0.05:0.06:100.
[0094] In step (2), the process conditions of ultrasonic oscillation are: 500W ultrasonic oscillation for 20 minutes.
[0095] In step (3), the specific process conditions of thermal spraying are: the spraying height is 55 cm from the substrate and the temperature is 130°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire gas path, the air pressure is 0.8 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.3 MPa.
[0096] In step (3), the flexible substrate is polyethylene terephthalate.
[0097] In step (4), the process conditions for the foaming treatment are: foaming at 250° C. for 80 minutes.
[0098] In step (4), the specific method of reduction is: placing 1 g of the foamed graphene oxide composite film flat in 8 g of a 5% potassium iodide solution, and oscillating ultrasonically at 70° C. and 200 W for 30 minutes.
[0099] In step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container reaches 20 MPa, maintain the pressure for 5 minutes, evacuate the container again, introduce hydrogen and maintain the pressure, and repeat this process 5 times.
[0100] Comparative Example 2
[0101] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0102] (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution;
[0103] (2) adding nanocellulose, silver nitrate and azodicarbonamide to the graphene oxide aqueous solution and oscillating the solution uniformly with ultrasonic waves to obtain a premixed solution;
[0104] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0105] (4) The graphene oxide composite film is then subjected to a foaming treatment, and then reduced using a potassium iodide solution. Finally, the composite film is sandwiched between two graphite sheets and transferred as a whole to a sealed container. The composite film is replaced using hydrogen to obtain the graphene-based thermal conductive film.
[0106] The specific method of step (1) is as follows: first, 1 g of graphene oxide, 0.8 g of magnesium powder, 1 g of diethylenetriamine, 0.05 g of N,N-diisopropylethylamine, and 0.1 g of 3% palladium carbon catalyst are added to 100 g of deionized water, stirred at 60° C. for reaction for 50 minutes, allowed to stand, filtered, washed, 100 g of deionized water is added, and ultrasonic vibration is performed evenly to obtain the graphene oxide aqueous solution.
[0107] The process conditions for standing still are: standing still at 4° C. for 30 minutes; the process conditions for ultrasonic oscillation are: ultrasonic oscillation at 500 W for 15 minutes.
[0108] In step (2), the mass ratio of nanocellulose, silver nitrate, azodicarbonamide and graphene oxide aqueous solution is 0.05:0.05:0.06:100.
[0109] In step (2), the process conditions of ultrasonic oscillation are: 500W ultrasonic oscillation for 20 minutes.
[0110] In step (3), the specific process conditions of thermal spraying are: the spraying height is 55 cm from the substrate and the temperature is 130°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire gas path, the air pressure is 0.8 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.3 MPa.
[0111] In step (3), the flexible substrate is polyethylene terephthalate.
[0112] In step (4), the process conditions for the foaming treatment are: foaming at 250° C. for 80 minutes.
[0113] In step (4), the specific method of reduction is: placing 1 g of the foamed graphene oxide composite film flat in 8 g of a 5% potassium iodide solution, and oscillating ultrasonically at 70° C. and 200 W for 30 minutes.
[0114] In step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container reaches 20 MPa, maintain the pressure for 5 minutes, evacuate the container again, introduce hydrogen and maintain the pressure, and repeat this process 5 times.
[0115] Comparative Example 3
[0116] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0117] (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution;
[0118] (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, then adding the modified carbon fiber, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution;
[0119] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0120] (4) The graphene oxide composite film is then subjected to a foaming treatment, and then reduced using a potassium iodide solution. Finally, the composite film is sandwiched between two graphite sheets and transferred as a whole to a sealed container. The composite film is replaced using hydrogen to obtain the graphene-based thermal conductive film.
[0121] The specific method of step (1) is as follows: first, 1 g of graphene oxide, 0.8 g of magnesium powder, 1 g of diethylenetriamine, 0.05 g of N,N-diisopropylethylamine, and 0.1 g of 3% palladium carbon catalyst are added to 100 g of deionized water, stirred at 60° C. for reaction for 50 minutes, allowed to stand, filtered, washed, 100 g of deionized water is added, and ultrasonic vibration is performed evenly to obtain the graphene oxide aqueous solution.
[0122] The process conditions for standing still are: standing still at 4° C. for 30 minutes; the process conditions for ultrasonic oscillation are: ultrasonic oscillation at 500 W for 15 minutes.
[0123] In step (2), the preparation method of the modified carbon fiber is as follows: first, 1 g of ethylene glycol monoethyl ether and 2 g of ethyl acetate are stirred and mixed, then 0.02 g of carbon fiber is added, heated and refluxed for 5 hours, centrifuged, washed, and dried to obtain the modified carbon fiber.
[0124] In step (2), the carbon content of the carbon fiber is greater than 95%, and the average length is 4 mm; the diameter of the nano carbon fiber is 8 nm, and the length is 1 μm.
[0125] In step (2), the mass ratio of modified carbon fiber, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.2:0.05:0.06:100.
[0126] In step (2), the process conditions of ultrasonic oscillation are: 500W ultrasonic oscillation for 20 minutes.
[0127] In step (3), the specific process conditions of thermal spraying are: the spraying height is 55 cm from the substrate and the temperature is 130°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire gas path, the air pressure is 0.8 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.3 MPa.
[0128] In step (3), the flexible substrate is polyethylene terephthalate.
[0129] In step (4), the process conditions for the foaming treatment are: foaming at 250° C. for 80 minutes.
[0130] In step (4), the specific method of reduction is: placing 1 g of the foamed graphene oxide composite film flat in 8 g of a 5% potassium iodide solution, and oscillating ultrasonically at 70° C. and 200 W for 30 minutes.
[0131] In step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container reaches 20 MPa, maintain the pressure for 5 minutes, evacuate the container again, introduce hydrogen and maintain the pressure, and repeat this process 5 times.
[0132] Comparative Example 4
[0133] A method for preparing a graphene-based thermally conductive film, the specific steps are as follows:
[0134] (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution;
[0135] (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, and then adding the modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution;
[0136] (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film;
[0137] (4) Then, the graphene oxide composite film is reduced using a potassium iodide solution to obtain the graphene-based thermal conductive film.
[0138] The specific method of step (1) is as follows: first, 1 g of graphene oxide, 0.8 g of magnesium powder, 1 g of diethylenetriamine, 0.05 g of N,N-diisopropylethylamine, and 0.1 g of 3% palladium carbon catalyst are added to 100 g of deionized water, stirred at 60° C. for reaction for 50 minutes, allowed to stand, filtered, washed, 100 g of deionized water is added, and ultrasonic vibration is performed evenly to obtain the graphene oxide aqueous solution.
[0139] The process conditions for standing still are: standing still at 4° C. for 30 minutes; the process conditions for ultrasonic oscillation are: ultrasonic oscillation at 500 W for 15 minutes.
[0140] In step (2), the preparation method of the modified carbon fiber is as follows: first, 1 g of ethylene glycol monoethyl ether and 2 g of ethyl acetate are stirred and mixed, then 0.02 g of carbon fiber is added, heated and refluxed for 5 hours, centrifuged, washed, and dried to obtain the modified carbon fiber.
[0141] In step (2), the carbon content of the carbon fiber is greater than 95%, and the average length is 4 mm; the diameter of the nano carbon fiber is 8 nm, and the length is 1 μm.
[0142] In step (2), the mass ratio of modified carbon fiber, nanocellulose, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.2:0.05:0.05:0.06:100.
[0143] In step (2), the process conditions of ultrasonic oscillation are: 500W ultrasonic oscillation for 20 minutes.
[0144] In step (3), the specific process conditions of thermal spraying are: the spraying height is 55 cm from the substrate and the temperature is 130°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire gas path, the air pressure is 0.8 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.3 MPa.
[0145] In step (3), the flexible substrate is polyethylene terephthalate.
[0146] In step (4), the specific method of reduction is: placing 1 g of graphene oxide composite film flat in 8 g of 5% potassium iodide solution, and oscillating ultrasonically at 70° C. and 200 W for 30 minutes.
[0147] Test example
[0148] The performance of the thermally conductive films obtained in Examples 1 to 3 and Comparative Examples 1 to 4 was investigated respectively, and the results are shown in Table 1.
[0149] Among them, the thermal conductivity is tested using a thermal conductivity dynamic measuring instrument; the thickness is measured using an atomic force microscope with a set temperature of 25°C and a pressure of 0.1MPa; and the mechanical properties are tested using a nanoindentation tester.
[0150] Table 1. Performance test results
[0151]
[0152] It can be seen from Table 1 that the thermally conductive films obtained in Examples 1 to 3 have high thermal conductivity, high tensile strength, and excellent thermal conductivity and mechanical properties.
[0153] In Comparative Example 1, the partial reduction treatment of graphene oxide in step (1) is omitted, in Comparative Example 2, the modified carbon fiber is omitted in step (2), in Comparative Example 3, the nanocellulose is omitted in step (2), and in Comparative Example 4, the foaming treatment and the hydrogen replacement treatment are omitted. The thermal conductivity of the obtained thermally conductive film is significantly lowered, indicating that the pretreatment of graphene oxide and the addition of modified carbon fiber, nanocellulose, hydrogen replacement and other steps synergistically improve the thermal conductivity of the product. In addition, the mechanical properties of the thermally conductive films obtained in Comparative Examples 1 to 3 are significantly deteriorated, indicating that the pretreatment of graphene oxide is beneficial to the reinforcement of carbon fiber and nanocellulose in the system, and carbon fiber and nanocellulose synergistically improve the mechanical properties.
[0154] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0155] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a graphene-based thermally conductive film, characterized in that: The specific steps are as follows: (1) firstly partially reducing graphene oxide to prepare a graphene oxide aqueous solution; (2) then modifying the carbon fiber with ethylene glycol monoethyl ether to obtain modified carbon fiber, and then adding the modified carbon fiber, nanocellulose, silver nitrate, and azodicarbonamide to the graphene oxide aqueous solution, and oscillating evenly with ultrasonic waves to obtain a premixed solution; (3) spraying the premixed liquid onto a flexible substrate using a thermal spraying method to obtain a graphene oxide composite film; (4) The graphene oxide composite film is then foamed, reduced with a potassium iodide solution, and finally sandwiched between two graphite sheets, transferred as a whole to a sealed container, and replaced with hydrogen to obtain the graphene-based thermal conductive film; In parts by weight, the specific method of step (1) is as follows: first, 1 part of graphene oxide, 0.8-1 part of magnesium powder, 0.8-1 part of diethylenetriamine, 0.05-0.08 part of N,N-diisopropylethylamine, and 0.08-0.1 part of 3-5% palladium carbon catalyst are added to 100 parts of deionized water, stirred at 50-60° C. for 50-70 minutes, allowed to stand, filtered, washed, and 100 parts of deionized water are added, and ultrasonic vibration is performed evenly to obtain the graphene oxide aqueous solution; In step (2), the preparation method of the modified carbon fiber is as follows, in parts by weight: first, 1 part of ethylene glycol monoethyl ether and 1 to 2 parts of ethyl acetate are stirred and mixed, then 0.02 to 0.04 parts of carbon fiber are added, heated and refluxed for 3 to 5 hours, centrifuged, washed, and dried to obtain the modified carbon fiber; In step (2), the mass ratio of modified carbon fiber, nanocellulose, silver nitrate, azodicarbonamide, and graphene oxide aqueous solution is 0.1-0.2: 0.05-0.08: 0.03-0.05: 0.06-0.09: 100; In step (2), the carbon fiber has a carbon content greater than 95% and an average length of 4 to 8 mm; the diameter of the nanocarbon fiber is 5 to 8 nm and the length is 1 to 2 μm; In step (4), the specific method of the replacement treatment is: first evacuate the sealed container, then introduce hydrogen until the pressure in the sealed container is 15-20 MPa, maintain the pressure for 5-8 minutes, evacuate the container again, introduce hydrogen and maintain the pressure, and repeat this 3-5 times.
2. The preparation method according to claim 1, characterized in that: In step (3), the specific process conditions of thermal spraying are: the spraying height is 45 to 55 cm from the substrate, and the temperature is 130 to 140°C; the spraying equipment used during spraying includes 3 regulating valves, one of which is a switch to control the air flow size of the entire air path, the air pressure is 0.6 to 0.8 MPa, and the remaining two are the main control valve and the auxiliary valve, and the air pressure is 0.3 to 0.5 MPa.
3. The preparation method according to claim 1, characterized in that: In step (3), the flexible substrate is polyethylene terephthalate or polybutylene terephthalate.
4. The preparation method according to claim 1, characterized in that: In step (4), the process conditions of the foaming treatment are: foaming at 200-250° C. for 80-100 minutes.
5. The preparation method according to claim 1, characterized in that: In step (4), the specific method of reduction is as follows, in parts by weight: placing 1 part of the foamed graphene oxide composite film flat in 5 to 8 parts of a 5 to 8% potassium iodide solution, and oscillating ultrasonically at 60 to 70° C. and 200 to 300 W for 30 to 40 minutes.
6. A graphene-based thermally conductive film obtained by the preparation method according to any one of claims 1 to 5.